Analisa Fundamental Makro dan Struktur Kepemilikan dengan Variabel Intervening Struktur Modal, Manajemen Laba, dan Kinerja Keuangan yang Berpengaruh terhadap Nilai Perusahaan - Vera Rambu Nggonngi; Hwihanus Hwihanus (Jurnal Riset Ekonomi dan Akuntansi, 2025)
The rapid development in the industrial world today has created intense competition among investors and business actors. Alongside economic growth, companies strive to showcase their best performance to enhance competitiveness, which often requires additional capital. This study aims to examine the influence of macro fundamentals, ownership structure, capital structure, earnings management, and financial performance on firm value. The results indicate that these variables have a significant impact on firm value.